Juvenile Homicide in the United States: Sizing Up the Problem and Moving Forward - Heide, Kathleen M. (Homicide studies, 2022)
Juvenile murder arrests in the United States increased dramatically from 1984 to 1993, leading experts to forecast an epidemic of continued violence. Juvenile arrests for murder from 1995 to 2019 are examined to assess whether this prediction was correct. Changes in the laws in response to juvenile violence and US Supreme Court cases that addressed constitutional limitations to the punishment of juvenile murderers are synthesized. The evolution of research on juvenile homicide offenders over the last two decades is highlighted. Recommendations about ways to move forward by using evidence-based practices to prevent juvenile violence and to reduce recidivism are discussed.